Prophetic Parenting Sebagai Paradigma Pendidikan Karakter - Styawati, Yuslia (Didaktika Religia, 2016)
Character education has become something that is extremely needed compared toprevious decades. Moral damages in the form of delinquency, robbery, violence,bulliying, corruption, and bribery become common today. In this instance,modern culture is unable to gadually and comprehensively overcome these socialpathologies, and even modern education makes these worse. Therefore, propheticparenting is an evolutionary solution to change this serious condition with futurevision, not an instant solution.